Penelitian pengaruh waktu penekanan dan tekanan terhadap daya rekat lem sintesis untuk kulit sol, kulit boks, dan pvc - Sunarso Hs; Bambang Oetojo (Majalah Kulit, Karet, dan Plastik, 1988)
Glue is valuable substance for sealing two things (compact thing). The research uses synthetic, and the adhesive strength reaches for sole leather, PVC to sole leather at the pressure of 30 bars, pressure duration 6 minutes (5,22 kg/10 cm2, and 5,68 kg/ 10 cm2), for PVC to PVC, box leather tp PVC at the pressure of 20 bars and pressure duration 6 minutes (5,98 kg/10 cm2 and 7,12 kg/10 cm2), whereas for box leather to sole leather at the pressure of 30 bars, pressure duration 9 minutes (4,36 Kg/10 cm2).